2023
DOI: 10.3390/ma16020570
|View full text |Cite
|
Sign up to set email alerts
|

Wood Residue-Derived Biochar as a Low-Cost, Lubricating Filler in Poly(butylene succinate-co-adipate) Biocomposites

Abstract: This study focused on the development of a novel biocomposite material formed by a thermoplastic biodegradable polyester, poly(butylene succinate-co-adipate) (PBSA), and a carbonaceous filler as biochar (BC) derived by the pyrolysis of woody biomass waste. Composites with various BC contents (5, 10, 15, and 20 wt.%) were obtained by melt extrusion and investigated in terms of their processability, thermal, rheological, and mechanical properties. In all the composites, BC lowered melt viscosity, behaving as a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The results showed that biochar exhibits a stable behavior, with a minimal mass loss of <15% up to 600 °C. This outcome was expected, given that biochar is already subjected to thermal degradation during the pyro-gasification process [ 18 ] The thermal profiles observed for biochar are typical of a pyrolyzed carbonaceous material derived from agricultural and forestry waste. The slow rate of mass loss observed in the thermograms was mainly attributed to the presence of refractory organic matter, degraded lignin, and strong C–C covalent bonds that are resistant to degradation [ 18 ].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The results showed that biochar exhibits a stable behavior, with a minimal mass loss of <15% up to 600 °C. This outcome was expected, given that biochar is already subjected to thermal degradation during the pyro-gasification process [ 18 ] The thermal profiles observed for biochar are typical of a pyrolyzed carbonaceous material derived from agricultural and forestry waste. The slow rate of mass loss observed in the thermograms was mainly attributed to the presence of refractory organic matter, degraded lignin, and strong C–C covalent bonds that are resistant to degradation [ 18 ].…”
Section: Resultsmentioning
confidence: 88%
“…Due to the increasing interest in ecofriendly and sustainable materials, biochar has been intensively studied as a promising filler and reinforcement in polymers [ 18 ]. Biochar is a byproduct of biomass pyrolysis and, thus, can be characterized as a biobased filler.…”
Section: Introductionmentioning
confidence: 99%
“…The PBS/BC composites exhibited a decreasing tendency in the storage modulus and complex viscosity with increasing filler content, which was more pronounced at lower frequencies. This was due to a lack of interfacial bonding between the PBS matrix and the BC, and the bonding was further reduced with increasing filler content, resulting in a decrease in the complex viscosity 28,29 . Therefore, the decrease in the complex viscosity with the addition of BC reduces the viscosity of the composite and improves its processability.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no significant shift or new bands attributable to chemical interactions between the filler and polymer matrix were observed. In conclusion, the addition of bran only reduced the intensity of significant PBSA peaks, indicating that bran acts as an inert filler [ 59 ].…”
Section: Resultsmentioning
confidence: 99%